Inclusive J/[psi] production in Xe-Xe collisions at √sNN=5.44 TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Deisting, Alexander; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Klewin, Sebastian; Köhler, Markus Konrad; Mercado Pérez, Jorge; et al. (Physics letters, 2018)
Inclusive J/ψ production is studied in Xe-Xe interactions at a centre-of-mass energy per nucleon pair of sNN=5.44 TeV, using the ALICE detector at the CERN LHC. The J/ψ meson is reconstructed via its decay into a muon pair, in the centre-of-mass rapidity interval 2.5<y<4 and down to zero transverse momentum. In this Letter, the nuclear modification factors RAA for inclusive J/ψ, measured in the centrality range 0-90% as well as in the centrality intervals 0-20% and 20-90% are presented. The RAA values are compared to previously published results for Pb-Pb collisions at sNN=5.02 TeV and to the calculation of a transport model. A good agreement is found between Xe-Xe and Pb-Pb results as well as between data and the model.
*ALICE collaboration: S. Acharya, V. Anguelov, M. Arslandok, M.C. Danisch, A. Deisting, V.J.G. Feuillard, P. Glässel, J. Kim, M. Kim, S. Klewin, M.K. Köhler, L. Leardini, J. Mercado Pérez, A. Ohlson, Y. Pachmayer, K. Reygers, R. Schicker, M.O. Schmidt, J. Stachel, D.F. Weiser, B. Windelband [und 996 weitere]
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, "NN" ist dabei tiefgestellt
Gesehen am 31.05.2019